(untitled) (Swiss Medical Weekly, 2011)
QUESTION UNDER STUDY: To assess how important the possibility to choose specialist physicians is for Swiss residents and to determine which variables are associated with this opinion. METHODS: This cross-sectional study used data from the 2007 Swiss population-based health survey and included 13,642 non-institutionalised adults who responded to the telephone and paper questionnaires. The dependent variable included answers to the question “How important is it for you to be able to choose the specialist you would like to visit?” Independent variables included socio-demographics, health and past year healthcare use measures. Crude and adjusted logistic regressions for the importance of being able to choose specialist physicians were performed, accounting for the survey design. RESULTS: 45% of participants found it very important to be able to choose the specialist physician they wanted to visit. The answers “rather important”, “rather not important” and “not important” were reported by 28%, 20% and 7% of respondents. Women, individuals in middle/high executive position, those with an ordinary insurance scheme, those reporting ≥2 chronic conditions or poorer subjective health, or those who had had ≥2 outpatient visits in the preceding year were more likely to find this choice very important. CONCLUSIONS: In 2007, almost half of all Swiss residents found it very important to be able to choose his/her specialist physician. The further development of physician networks or other chronic disease management initiatives in Switzerland, towards integrated care, need to pay attention to the freedom of choice of specialist physicians that Swiss residents value. Future surveys should provide information on access and consultations with specialist physicians.